Performance improvement through digital accounting for MSME sustainability - Hayatunnisah, Fera; Chaerunnisa, Annisa; Wiradinata, Rochanda; Rusdiyana, Rusdiyana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but still face various challenges, especially in financial management and utilization of digital accounting technology. This study aims to analyze the effect of improving performance and utilizing digital accounting on the sustainability of MSMEs in Cirebon City. Using a quantitative approach, respondents were taken from the culinary field and the fashion field. The subjects used for this study were 30 respondents (50% in the culinary field and 50% in the fashion field), the data were collected through distributing questionnaires to MSME players and analyzed using multiple regression and T-test. The results of the research conducted show that improving MSME performance has a significant effect on the sustainability of MSMEs with a contribution of 97.1%, while on the other hand digital accounting does not show a significant effect partially on the sustainability of MSMEs. However, simultaneously the two variables explain 94.9% in the sustainability of MSMEs. This finding is different from previous findings because digital accounting is not significant, the main problem that arises is due to the lack of socialization and training in the use of digital accounting, infrastructure limitations, and other constraints such as on the internet. This study emphasizes the importance of performance improvement as the key to the sustainability of MSMEs and the need for a strategic approach in the implementation of digital accounting. The study recommends training and technical support to improve the effectiveness of digital accounting in supporting MSME competitiveness